Construction of multivariate regression analysis method with fuzzy hierarchies in the input data - Серая, Оксана Владимировна (Eastern-European Journal of Enterprise Technologies, 2009)
A method of calculating the parameters of multivariate regression equations based on the results of expert evaluation of pairwise comparisons of significant factors is offered. The case where the results of the comparison are fuzzy numbers is considered